Path Clearing, Policy Acceleration or Trend Reinforcement: Potential Implications of Selected Local Government Responses to Covid-19 in the UK - Tony Gore; Emma Bimpson; Julian Dobson; Stephen Parkes (International Review of Public Policy)
Since its onset in 2020 Covid-19 impacts have engendered rapid interventions across all policy domains and at all scales of government. This has prompted lively debate around the wider significance and longer-term implications of such moves with regard to their role as potential 'punctuations' within a broader policy paradigm shift. This includes acting as a ‘path-clearing’ mechanism that heralds a move towards a different approach; representing the onset of ‘path deviation’ towards such a change; quickly adding to the implementation of new ideas in a process of 'policy acceleration’; or essentially replicating existing patterns to provide 'trend reinforcement'. This paper applies these concepts to a wide range of evidence on local government responses to Covid-19 across the United Kingdom (UK). The analysis focuses on five selected domains: supporting and coordinating mutual aid; maintaining local economies; addressing homelessness; managing parks and other public spaces; and promoting active travel through road space reallocation. Developments in each of these areas are framed by both wider operational and existing policy contexts, as well as with respect to geographical and sectoral variations. The conclusion is that evidence exists for all four types of 'punctuation', but the patterns are inconsistent both between and within different local authorities and policy domains.